Job Analysis and Design of Educational Jobs in Indonesia - Bunyamin, Bunyamin; Nursyamsiah, Nursyamsiah; Umma, Rachmatul; Dearanti, Muti (Universitas Negeri Semarang, 2021)
Human resource management is required to enhance the effectiveness and creation of a suitable organizational system in sustaining the culture and organizational climate. In order to establish optimal job qualities that influence the quality of work life in an organization, it is important to comprehend job design. The purpose of this study is to describe the job analysis and design of education work at the educational unit level. The method used is descriptive qualitative by describing the problem clearly with the source of the library research with metaphysical realism as the approach. The data sources of this research are secondary data, including journals, online newspapers, web and literature books related to job analysis and educational work design, both domestic and foreign sources. Job analysis has an important role in an educational organization in order to place people in a certain position or position. With job analysis, school organizations can form effective human resource procedures to select, promote, train, assess and provide compensation. Job designs are made by schools to organize tasks that are on target, assign tasks to people with the abilities and skills that must be possessed to do these tasks in order to achieve the vision and mission of the school.